Composite Material over Steel in Automobile Industry - Jaskirat Singh, Pulkit Jain (International Journal of Advanced Science and Technology, 2020)
The Automobile Industries now finds a way out of reducing the weight of loading vehicles. This could be possible by using composite materials in place of steel or any other heavy substance. Some researches proofs that composite materials can be stronger then steel or any other metal as it is high in strength to weight ratio, corrosion resistance, and contains tailor-able properties. The Automobile Industry now keen to use composite fibered leaf springs in place of heavy steel leaf springs. The main objective of this review paper is to conclude the use of composite materials in Automobiles.